Adaptasi Visual Momiji dengan Teknik Crochet pada Produk Fashion - Puspitasari, Feny; Amalia, Annisa; Rahmah, Yumeida (Telkom University, 2023)
The adaptaton of traditonal culture and art to inspiraton in the fashion industry has become an increasing trend. In meetng these needs, it is not uncommon for designers to be inspired by nature’s charm creatvely and aesthetcally. Related to this, researchers will try to make a fashion product design in the form of combining traditonal elements with a modern touch, namely making a party dress by adaptng the visuals of Momiji with the crochet technique. The visual adaptaton of Momiji, which refers to the characteristcs of autumn in Japanese culture, is integrated with the crochet knitng technique to create a party wear product with a modern look. This study aims to combine Momiji’s unique aesthetc, such as colorful autumn leaves and motfs, with crochet techniques that give a dimension of texture and sofness to products and give a warm impression in accordance with the nuances of autumn in a modern look. This research method is a qualitatve research with a visual adaptaton technique approach, with the stages of analyzing Momiji’s motfs and colors which are then followed by a creatve process startng from making product concepts, moodboards, to real products. in this research is also equipped with the distributon of questonnaires to select products that will be made as a real product and measure the suitability of the resultng product with the established concept. The results of the study show that Momiji’s visual adaptaton with the crochet technique on party wear products with the theme ‘Warm Night in Tokyo’ can be realized in the form of colors, motfs, and textures with a modern look in the form of a midi dress complemented by a bolero. The product that was created has a suitability level with the theme as a structural design of 94%, a suitability of the product theme in color of 91%, a suitability of the product theme in the look of 90%, and a suitability of the product theme in texture of 86%.